Wielkość ochładzająca powietrza - na Wybrzeżu Klifowym w rejonie Białej Góry - w sezonach letnich 2008-2009 (Woliński Park Narodowy) - Szyga-Pluta, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The study includes an analysis of daily distribution of air cooling values in the selected locations of Wolin National Park. The measurements were taken in the summer seasons of 2008 and 2009. The index has been determined with regard to local qualities of the environment. It has been established that the described bioclimatic index possesses a varied daily distribution which depends on relief and vegetal coverage of the terrain. According to the scale of Conrad, the most favourable bioclimatic conditions occurred at location 1 (Beach). The daily distribution of air cooling values reflects thermal conditions and dampness. The most balanced distribution of air cooling values occurred at location 3 (Buczyna), which results from the smallest variation of temperature and dampness at this point as well as it being shielded from the wind.
Keywords: air cooling value; Biała Góra; Wolin National Park